Isotopic Age of the Xiong’er Group Volcanic Rocks and Its Geological Significance in Western Henan, China - Wenchao Dong; Xucheng Pang; Weixun Qu; Guangshun Hou (Geofluids)
The Xiong’er Group is mainly distributed in western Henan, southern Shanxi, and southeastern Shaanxi. As a set of low-grade metamorphic and low-deformation volcanic rocks formed in the transition period during the tectonic evolution of the North China Craton in the Precambrian, the tectonic and magmatic evolution information of this period are well recorded. The accurate isotopic dating of the Xiong’er Group has great significance to the study of the stratigraphic division and formation of volcanic rocks in the Xiong’er Group and the improved cognition of regional tectonic magmatism. In this study, through the SHRIMP (sensitive high-resolution ion microprobe) zircon uranium-lead (U-Pb) isotope dating of the volcanic rocks of the Xiong’er Group in the Xiong’er Mountain, the research results showed that the age data were separated into two intervals, the magmatic zircon ages from 1836 to 1711 Ma and the inherited zircon ages from 2415±19 to 2193±34 Ma. The isotopic age of magmatic zircon was considered to represent the formation age of the Jidanping Formation in the Xiong’er Mountain, and the isotopic ages of the inherited zircons were consistent with the formation ages of the Taihua Group supracrustal rocks in the lower Xiong’er Group. Combined with previous studies on isotope and rock geochemistry of volcanic rocks in the Xiong’er Group, it was believed that the formation ages of the volcanic rocks of the Xiong’er Group are between 1874 and 1618 Ma, among the ages of the Xushan Formation, Jidanping Formation, and Majiahe Formation, which were concentrated between 1874 and 1800 Ma, 1836 and 1711 Ma, and 1780 and 1618 Ma, respectively. The age of inherited zircon in the volcanic rocks of the Xiong’er Group indicated that the formation of the volcanic rocks of the Xiong’er Group had the addition of stratigraphic materials from the Taihua Group.